An in-depth comparative study of various plant-based protein-alginate complexes in the production of hemp seed oil microcapsules by supercritical carbon dioxide solution-enhanced dispersion - Gholivand, Somayeh; Tan, Tai Boon; Mat Yusoff, Masni; Choy, Hew Weng; Teow, Shuh Jun; Wang, Yong; Liu, Yuanfa; Tan, Chin Ping (Elsevier, 2024)
This study focuses on the microencapsulation of hemp seed oil (HSO) using a range of wall materials derived from plant-based proteins including hemp seed protein isolate (HPI), pea protein (PPI) and soy protein (SPI) in complexation with alginate (AL). The microencapsulation process was accomplished through the utilization of supercritical carbon dioxide solution-enhanced dispersion with water as a co-solvent. According to the results, both HPI/AL and PPI/AL microcapsules exhibited comparable and satisfactory properties in terms of water activity (5.26% and 5.33%), particle size (7.86 μm and 9.61 μm) and bulk density (0.363 g/mL and 0.349 g/mL). However, the overall findings highlighted the superiority of HPI/AL complex in producing microcapsules with the highest microencapsulation efficiency (90.56%), a spherical shape free from pores or fissures and an exceptional glass transition temperature. Furthermore, HPI/AL microcapsules displayed stronger antioxidant activities and oxidative stability, enhancing product shelf life significantly when compared to PPI/AL and SPI/AL microcapsules. © 2024 Elsevier Ltd